AN ANALY ILLOCUTIONA LYZSIS OF LOCUTIONARY AND ARY ACTS APPLIED IN ROBIN HOOD MOVIE - LAKSONO, FEBRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Pragmatics, Speech act, Locutionary Acts, Illocutionary Acts, Movie,Context, and Robin Hood MovieLanguage is the main tool used in sending a message to other person, to communicate ideas, thoughts and opinions. Pragmatics concerns with how people use language and consider how the speakers use the language in the social interaction with others. In pragmatics, there is a discussion of speech act theory basically focused on how meaning and action are related to language in communities. The researcher analyzes the types of locutionary acts and illocutionary acts based on utterances of main character in the Robin Hood (2010) movie. In this research study, there are two problems: (1) What are the locutionary acts found in the utterances of the main character in the Robin Hood 2010 movie, (2) What are the illocutionary acts performed in the utterances of the main character in Robin Hood 2010 movie. This study used qualitative approach to identify and examine the Robin Hood movie containing material that consists of types of speech act. The data used in this research were the main character utterances. The steps of analyzing data were classifying and determining the data, analyzing and describing the data, making a table and drawing conclusion.The results show 27 utterances contained speech act in scene 59 until 68 that the mostly produced was declarative sentence by 16 times while, the interrogative used 10 times and the imperative used for eight times for the type of locutionary acts.  For illocutionary acts exercitives used for 16 times, expositives used for 10 times, verdictives used for four times, behabitives used for three times and commissives used only once.There are suggestions proposed by the writer for the readers and next researchers. It helps to get further information about the importance of understanding the speech act theory and also the next researchers may analyze the objects were not only in the movie but also the other objects.